EVALUATION OF HIGH SCHOOL FINANCIAL REPORTING (Case Study in State High School 2 Lamongan) - Susanti, Dian Elita; Saraswati, Erwin (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to evaluate high school financial reporting. This research describe financial reporting of high school (case study in state high school 2 Lamongan). The financial report was evaluated based on SAK and regulations ministry of education and culture.This research used  case study research in state high school 2 Lamongan. This research use decription method. The sample that used in this research are financial reporting on March 2015. Data were analyzed by qualitative method. The result of high school financial reporting of state high school 2 Lamongan is financial reporting appropriate with based on regulations ministry of education and culture. State high school 2 Lamongan report education fund through SPJ. Financial reporting of state high school 2 Lamongan has not yet published financial statements. Financial reporting of state high school 2 Lamongan based on SAK is not effective   Key word        : Financial Reporting, High School, SAP